THE INFLUENCE OF LEARNING STYLES (VISUAL) ON TEACHING HOW TO WRITE IELTS TASK 1 ESSAY - Arofat Mukhtorkizi Ganikhujaeva (Research Parks Publishing LLC, 2021)
Learning style is a term pointing out the variations of cognitive nature in the process of second language acquisition. It is the way toward which the learners show a big preference in especially understanding, forming ideas, organizing and remembering the data connected with learning a particular language. As for the statement of Cornett (1983) learning styles are global approaches such as global or analytic, auditory or visual, which are used by the students learning a new language or other subject. Moreover, Brown (2000) states that learning styles’ role in giving explanations to justify why some L2 learners achieve more success than others has not been founded well, it constitutes a complex communication with specific L2 contexts in learning. Likewise, Ehrman (1996) mentions that learning styles are not opposite to each other yet they normally operate on a multiple continua; for instance, a person may be more sociable than reversed, or more close than open, or may have equal visual and auditory styles but without much kinesthetic and tactile engagement.